2012
DOI: 10.1016/j.clineuro.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical safety and primary efficacy of bone marrow mesenchymal cell transplantation in subacute spinal cord injured patients

Abstract: Background: In recent years, some studies were conducted to evaluate the effects of stem cells from different sources on patients with spinal cord injury (SCI). This study was carried out to evaluate the feasibility and therapeutic potential of autologous bone marrow cell (BMC) transplantation in 11 complete spinal cord injured patients at thoracic level. Methods and materials: This nonrandomized clinical trial compared the results of autologous BMC transplantation into cerebrospinal fluid (CSF) via lumbar pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(112 citation statements)
references
References 36 publications
(71 reference statements)
2
107
0
3
Order By: Relevance
“…Since 2005, a number of clinical trials have evaluated the safety and efficacy of autologous bone marrow cell transplantation in acute and chronic SCI patients (Deda et al, 2008;Geffner et al, 2008;Jarocha et al, 2014;Karamouzian et al, 2012;Park et al, 2005;Sykova et al, 2006;Yoon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2005, a number of clinical trials have evaluated the safety and efficacy of autologous bone marrow cell transplantation in acute and chronic SCI patients (Deda et al, 2008;Geffner et al, 2008;Jarocha et al, 2014;Karamouzian et al, 2012;Park et al, 2005;Sykova et al, 2006;Yoon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies however have elucidated their heterogeneity and the changes exhibited by these cells following SCI, thereby underscoring the need to preserve their normal physiological functions. Studies mentioned above, as well as other studies that are not detailed here, are indicative of the growing appreciation of cell transplantation therapies for therapeutically targeting astrocytes in SCI.With a special focus on chronic SCI conditions, many clinical trials based on the transplantation of unmodified mesenchymal, neural or bone-marrow stem cells have been launched around the world [167][168][169][170][171] . Among phase 1 studies, most of them have focused on safety measurements and graft survival according to different routes of administration (mostly intrathecal…”
mentioning
confidence: 99%
“…Several studies have reported sensory and motor improvements after 1-3 mo of stem cell transplantations combined with various other cells and growth factors [117][118][119][120][121] . In contrast, Karamouzian et al [122] stated that despite the feasibility and safety of cellular transplantations, the improvements in terms of functional recovery were not statistically significant in their study [122] . The low numbers of patients in these studies make it difficult to provide a definitive statement on the clinical potential of stem cell transplantation for SCI.…”
Section: Spinal Cord Injurymentioning
confidence: 63%